Analysis of the injuries of Korean professional basketball players during the 2019-2020 regular season - Song,M.; Choi, S.; Kim, H.; Kim, Y.; Lee, S.; Kang, H. (The Korean Journal of Sports Medicine, 2020)
Purpose: This study aimed to provide the descriptive statistics regarding the injury epidemiology of Korean professional basketball players.